Validation Study of the Revised Spirituality and Spiritual Care Rating Scale (SSCRS): A Cross-Sectional Survey in Poland - Panczyk M; Kwiećkowska L; Dobrowolska B; Borowiak E; Dyk D; Grochans E; Kozieł D; Kózka M; Kulik H; Lewko J; McSherry W; Gotlib J; et al. (Journal of Multidisciplinary Healthcare, 2023)
Mariusz Panczyk,1 Lucyna Kwiećkowska,1 Beata Dobrowolska,2 Ewa Borowiak,3 Danuta Dyk,4 Elżbieta Grochans,5 Dorota Kozieł,6 Maria Kózka,7 Halina Kulik,8 Jolanta Lewko,9 Wilfred McSherry,10 Joanna Gotlib,1 Mariusz Jaworski1 1Department of Education and Research of Health Sciences, Faculty of Health Sciences, Medical University of Warsaw, Warsaw, Poland; 2Department of Holistic Care and Management in Nursing, Faculty of Health Sciences, Medical University of Lublin, Lublin, Poland; 3Department of Conservative Nursing, Faculty of Health Sciences, Medical University of Lodz, Lodz, Poland; 4Department of Anaesthesiology and Intensive Care Nursing, Faculty of Health Sciences, Poznan University of Medical Sciences, Poznan, Poland; 5Department of Nursing, Faculty of Health Sciences, Pomeranian Medical University, Szczecin, Poland; 6Collegium Medicum, Jan Kochanowski University, Kielce, Poland; 7Department of Clinical Nursing, Faculty of Health Sciences, Jagiellonian University Collegium Medicum in Krakow, Krakow, Poland; 8Department of Nursing Propedeutics, School of Health Sciences, Medical University of Silesia in Katowice, Katowice, Poland; 9Department of Primary Health Care, Medical University of Bialystok, Bialystok, Poland; 10Department of Nursing, School of Health, Science and Wellbeing, Staffordshire University, Stoke-on-Trent, UKCorrespondence: Mariusz Panczyk, Department of Education and Research of Health Sciences, Faculty of Health Sciences, Medical University of Warsaw, Litewska 14/16 St, Warsaw, 00-581, Poland, Tel +48 22 57 20 490, Fax +48 22 57 20 491, Email mariusz.panczyk@wum.edu.plIntroduction: The use of a validated scale, Spirituality and Spiritual Care Rating Scale (SSCRS) to measure nurses’ perceptions of spirituality and spiritual care.Aim: The purpose of this study was to analyse selected psychometric properties of the Polish version of the SSCRS, among them the applicability of the dimensions of spiritual care in nursing, ie, spirituality, spiritual care, religiosity and personalized care, to Polish conditions.Methods: Poland-wide multicentre study with a cross-sectional validation design. The study was conducted between March and June 2019. Seven Polish Nursing Faculties accepted the invitation to participate in the study. A representative sample of 853 nurses enrolled in MSc (postgraduate) programs in nursing participated. After translation and cultural adaption of the SSCRS, the instrument underwent a full psychometric evaluation of its construct validity using (exploratory and confirmatory factor analysis), internal consistency (Cronbach’s alpha and correlation analysis), reliability (test−retest analysis), known-group validity (Student’s t-test) analysis.Results: The exploratory and confirmatory factor analysis demonstrated that the Polish version of the SSCRS was a three-factor model with “Activity-centred spiritual care” (9 items), “Emotional support-centred spiritual care” (5 items) and “Religiosity” (3 items) domains. The Cronbach’s alpha coefficient for the whole scale was 0.902, and the alpha values for the individual domains were 0.898, 0.873 and 0.563, respectively. The three domains mentioned above seemed to provide a comprehensive understanding of spiritual care perceived subjectively by Polish MSc in nursing students.Conclusion: This study demonstrated a substantial degree of similarity in the selected psychometric characteristics of the Polish version of SSCRS and the original scale.Keywords: spirituality, holistic nursing, nursing care, postgraduate nursing education